The doll's house Henrik Ibsen - Video Classroom (Victoria : Learning Essentials, 1989)
Summary: Examines the play treatment of marriage, women's rights and the questions of freedom, honesty and independence.
Presenter: Dr. Alan Dilnot, Monika Siggins
Keywords: Literature -- Study and teaching; Literature